The Role of Gamma-Delta T Cells in Diseases of the Central Nervous System - Wo, Jin; Zhang, Feng; Li, Zhizhong; Sun, Chenghong; Zhang, Wencai; Sun, Guodong (Frontiers in Immunology, 2020)
Gamma-delta (γδ) T cells are a subset of T cells that promote the inflammatory responses of lymphoid and myeloid lineages, and are especially vital to the initial inflammatory and immune responses. Given the capability to connect crux inflammations of adaptive and innate immunity, γδ T cells are responsive to multiple molecular cues and can acquire the capacity to induce various cytokines, such as GM-CSF, IL-4, IL-17, IL-21, IL-22, and IFN-γ. Nevertheless, the exact mechanisms responsible for γδ T cell proinflammatory functions remain poorly understood, particularly in the context of the central nervous system (CNS) diseases. CNS disease, usually leading to irreversible cognitive and physical disability, is becoming a worldwide public health problem. Here, we offer a review of the neuro-inflammatory and immune functions of γδ T cells, intending to understand their roles in CNS diseases, which may be crucial for the development of novel clinical applications.